Analisis Strategi Akuntansi Manajemen dan Pengaruhnya Terhadap Volume Penjualan PT Solo Murni - Intania Maharani; Desy Nur Pratiwi; Yuwita Ariessa Pravasanti (ITB AAS INDONESIA, 2022)
This research aims to determine the influence of management accounting strategies in increasing sales volume at PT Solo Murni. The strategies studied include management accounting information system, promotion and brand image. The type of data used in this study is primary data in the form of questionnaires that are shared against samples that have been calculated by slovin formula so that a total of 110 employees of PT Solo Murni were obtained on ppic staff, production administration, and supervisors as samples.The data analysis method used in this study is Multiple Linear Regression using SPSS (Statistical Packages for the Social Science) version 23.00. The results of the data analysis showed that partially management accounting information system and brand image had a significant impact on sales volume at PT Solo Murni. Meanwhile, partial promotions have no effect and are insignificant to sales volume. Simultaneous testing of all three variables showed that management accounting system, promotion and brand image significantly affected 54.9% of sales volume at PT Solo Murni. Thus, other innovative strategies are needed in order to increase sales volume at PT Solo Murni.